2005
DOI: 10.1021/ic048251m
|View full text |Cite
|
Sign up to set email alerts
|

Substituent-Directed Structural and Physicochemical Controls of Diruthenium Catecholate Complexes with Ligand-Unsupported Ru−Ru Bonds

Abstract: A family of diruthenium complexes with ligand-unsupported Ru-Ru bonds has been systematically synthesized, and their crystal structures and physical properties have been examined. A simple, useful reaction between Ru2(OAc)4Cl (OAc- = acetate) and catechol derivatives in the presence of bases afforded a variety of diruthenium complexes, generally formulated as [Na(n){Ru2(R4Cat)4}] (n = 2 or 3; R4 = -F4, -Cl4, -Br4, -H4, -3,5-di-t-Bu, and -3,6-di-t-Bu; Cat(2-) = catecholate). The most characteristic feature of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…In sharp contrast, only a moderate conversion 60 % of catechol was obtained to give cyclohexanol as a predominant product under the same reaction conditions, suggesting a catalyst deactivation by means of formation of ruthenium-catecholate complexes from ruthenium trichloride and bidentate ligand catechol ( Table 5, run 4). [34][35][36] In addition, under the same conditions (Ru 6 mol%, 240 8C, 3-5 h), Ru/A-H 3 PO 4 was effective in the HDO of more complicated branched phenols with hydroxyl and alkoxy groups, affording cyclohexane in high to medium yields ( Table 5, runs 5-11). Moreover, with the optimized reaction conditions, a series of representative bioderived phenolic monomers, the most abundant aromatic units originating from bio-oil, were efficiently converted to hydrocarbons as well ( Table 5, runs 12-18).…”
Section: Hdo Of Phenol Derivativesmentioning
confidence: 89%
“…In sharp contrast, only a moderate conversion 60 % of catechol was obtained to give cyclohexanol as a predominant product under the same reaction conditions, suggesting a catalyst deactivation by means of formation of ruthenium-catecholate complexes from ruthenium trichloride and bidentate ligand catechol ( Table 5, run 4). [34][35][36] In addition, under the same conditions (Ru 6 mol%, 240 8C, 3-5 h), Ru/A-H 3 PO 4 was effective in the HDO of more complicated branched phenols with hydroxyl and alkoxy groups, affording cyclohexane in high to medium yields ( Table 5, runs 5-11). Moreover, with the optimized reaction conditions, a series of representative bioderived phenolic monomers, the most abundant aromatic units originating from bio-oil, were efficiently converted to hydrocarbons as well ( Table 5, runs 12-18).…”
Section: Hdo Of Phenol Derivativesmentioning
confidence: 89%
“…Excitation with a 395 nm, ∼120 fs pulse resulted in an instantaneous bleach Figure 12. TRIR data obtained in CH 2 Cl 2 following excitation with a 400 nm, ∼150 fs laser pulse: (a) a series of TRIR spectra for the mononuclear complex 5, recorded at -50, 1, 2, 3, 7, 35, 100, 200, 400, and 1000 ps time delays after the laser pulse; (b) a series of TRIR spectra for the binuclear complex 2, recorded at 2, 3, 7, 15,35,75,200, and 400 ps time delays after the laser pulse; (c) initial parts of the kinetic trace recorded at 1570 cm -1 , which demonstrate the presence of a grow-in component for 2, the parent bleach recovery of ν(CO) at 1639 cm -1 for 5, and the decay of the corresponding transient band at 1620 cm -1 for 5.…”
Section: Articlementioning
confidence: 99%
“…The Na + cations are further chelated by DME (1b) or coordinated by THF (2b s ), exhibiting a distorted octahedral or tetrahedral coordination geometry. On the other hand, the second mode, called the "out-of-plane connection", was found in [Na (THF) 11,12 (Figure 1b). The Na The connecting structures of the Na + cations to the [Ru 2 (R 4 Cat)] 2-/3units are among the fascinating features of the present complexes, especially for the development of molecular assemblages based on cation‚‚‚anion interactions.…”
Section: Physical Measurementsmentioning
confidence: 99%
“…6 On the other hand, the effects of cations on structures and physical properties in the solid state and solution have been less well-described for dimetallic com- plexes accompanying by countercations represented by [M 2 X 8 ] n-(X ) halogen atom), 7 [M 2 (CO 3 ) 4 ] n-, 8 [M 2 (SO 4 ) 4 ] n-, 9 and [M 2 (HPO 4 ) 4 ] n-. 10 In the preceding paper of this series, 11 we reported the synthesis and the structural and physicochemical diversity of a variety of diruthenium complexes, generally formulated as [Na n {Ru 2 (R 4 Cat) 4 }] (n ) 2 or 3; R 4 ) F 4 , Cl 4 , 12 Br 4 , H 4 , 3,5-di-t-Bu, and 3,6-di-t-Bu), and clearly demonstrated that the complexes with ligand-unsupported Ru-Ru bonds can sensitively respond to redox reactions and ligand substituents on the basis of the greater degree of freedom in their molecular structures. Although special attention had not been paid to the interaction between the [Ru 2 (R 4 Cat) 4 ] 2-/3units and countercations in the literature, the countercations, Na + , bind to the O Cat atoms of R 4 Cat 2in all of the complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation